Visual outcome following clear corneal incision phacoemulsification with rigid intra-ocular lens and small incision cataract surgery in low socioeconomic group patients: A comparative analysis in a teaching hospital in South India - Warad, Chethana; Parul; Sivakrishna, Pavuluri; Arvind L Tenagi; Bhagyajyothi B Khanagavi; Swikrity Chakraborty (Asian Journal of Medical Sciences, 2023)
Background: Cataract is the most common cause of curable blindness worldwide. Aims and Objectives: A comparative analysis of clear corneal phacoemulsification with rigid intra-ocular Lens (IOL) and small incision cataract surgery (SICS) in low socioeconomic group patients in terms of post-operative visual outcome, surgically induced astigmatism (SIA), and intra-and post-operative complications. Materials and Methods: A prospective hospital-based comparative study was conducted for 8 months in 424 eyes of 400 senile cataract patients divided into PHACO and SICS groups. Each group consisted of 212 eyes of 200 patients. Detailed examinations for best corrected visual acuity (BCVA), SIA, and complications were evaluated on the 1st post-operative day, 1st week and 6 weeks postoperatively. Results: BCVA 6\18 or higher was 95.38% in the phacoemulsification group and 94.81% in the SICS group. The study revealed good visual outcome in both SICS and Phaco groups with no significant difference. The mean SIA was more in SICS group (−0.96±0.57) than in phaco group (−0.71±0.47) which was statistically significant. In terms of complications, no significant difference was noted between the groups. Conclusion: The outcome of this study indicated that though SIA is more in SICS group than Phaco group, there is no difference between the groups in terms of visual outcome. The study has proven that SICS has comparable effectiveness as phacoemulsification with rigid IOL, which should be considered in low- and middle-income countries.